Metabolic Phenotype of Daphnia Under Hypoxia: Macroevolution, Microevolution, and Phenotypic Plasticity - Lee, Tingyat M.; Westbury, Kurtis M.; Martyniuk, Christopher J.; Nelson, William A.; Moyes, Christopher D. (Frontiers in Ecology and Evolution, 2022)
Daphnia is a freshwater crustacean that is able to upregulate hemoglobin (Hb) in response to hypoxia, imparting a red color. We combine multiple field surveys across season with a lab experiment to evaluate changes in the metabolic phenotype of Daphnia in relation to environmental hypoxia. Looking at the zooplankton community, we found that D. pulicaria was restricted to lakes with a hypoxic hypolimnion. Comparing D. pulicaria with different amounts of Hb, red animals showed higher mRNA levels for several Hb genes, whereas most glycolytic genes showed red/pale differences of less than 50%. We also observed seasonal changes in the metabolic phenotype that differed between red and pale animals. Hb was upregulated early in the season in hypoxic lakes, and a relationship between Hb and lactate dehydrogenase only emerged later in the season in a temporal pattern that was lake specific. To evaluate whether these differences were due to specific lake environments or microevolutionary differences, we tested the induction of genes under controlled hypoxia in isofemale lines from each of four lakes. We found a strong response to 18 h hypoxia exposure in both Hb and lactate dehydrogenase mRNA, although the magnitude of the acute response was greater than the steady state differences in mRNA levels between pale and red Daphnia. The baseline expression of Hb and lactate dehydrogenase also varied between isofemale lines with different lake origins. These results, in combination with comparison of glycogen measurements, suggests that Hb functions primarily to facilitate oxygen delivery, mitigating systemic hypoxia, rather than an oxygen store. The combination of lab and field studies suggest that the metabolic phenotype of the animal is influenced by both microevolutionary differences (within and between lakes) as well as the spatial and temporal environmental heterogeneity of the lakes. The differences between Daphnia species, and the unexpected lack of hypoxia sensitivity of select glycolytic genes provide evidence of macroevolutionary differences in metabolic strategies to cope with hypoxia.